Estudo in vitro: microinfiltração marginal em restaurações com resina composta classe II - Calizaya-Bendita, Danny; Chávez-Fernández, Fernando; Loaiza-Jara, Lizeth; Molina-Arraya, Evelyn; Mamani-Cori, Vilma; Poma, Ronald (Revista Acciones Médicas, 2022)
Objective: to evaluate in vitro marginal microleakage in class II composite resin restorations in posterior teeth. Method: A quasi-experimental design study of longitudinal section was carried out, the sample consisted of 40 healthy upper and lower posterior teeth (premolars and molars), these were extracted for orthodontic or periodontal indications and have been preserved in distilled water for 48 hours; Those teeth that had occlusal restorations or any alteration in shape or structure were excluded. The teeth were randomly distributed in 02 experimental groups. Experimental group 1 (GE1) received the restoration with class II composite resin with ionomer base and experimental group 2 (GE2) received the restoration with class II composite resin without ionomer base. Results: when comparing the degree of marginal microleakage between GE1 and GE2 at 48 hours, 15 days, 30 days and 45 days with a confidence level of 95%, there is a statistically significant difference (p < 0.05), that is to say that, there is a higher degree of marginal microleakage in restorations with class II composite resin without ionomer base. Conclusion: Class II composite resin restorations in posterior teeth that did not have an ionomeric base have a higher degree of marginal microleakage.
Keywords: ionomeric base; marginal microfiltration; dentistry; composite resin